Photoreceptor-specific loss of perifoveal temporal contrassensitivity in retinitis pigmentosa - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan (Translational Vision Science & Technology, 2020)
Purpose: Inherited retinal diseases affect the L-, M-, S-cones and rods in distinct ways, which calls for new methods that enable quantification of photoreceptor-specific functions. We tested the feasibility of using the silent substitution paradigm to estimate photoreceptor-driven temporal contrast sensitivity (tCS) functions in patients with retinitis pigmentosa. Methods: The silent substitution paradigm is based on substitution of lights of different spectral composition; this offers considerable advantage over other stimulation techniques. We used a four-primary LED stimulator to create perifoveal annular stimuli (2° inner, 12° outer diameters) and used a triple silent substitution to probe photoreceptor-selective tCS. Measurements were performed in a heterogeneous cohort of 15 patients with retinitis pigmentosa and related to those in a control group of nine color-normal healthy observers. Age differences between groups were addressed with a model of age-related normal contrast sensitivity derived from measurements in 20 healthy observers aged between 23 and 83 years. Results: The age-related loss of tCS amounted to 0.1 dB/year in healthy subjects across all photoreceptor subtypes. In patients, tCS was decreased for every photoreceptor subtype; however, S-cone-and rod-driven sensitivities were most strongly affected. Postreceptoral mechanisms were not affected. Conclusions: This feasibility study provides evidence that the silent substitution technique enables the estimation of photoreceptor-selective tCS functions and can serve as an accurate biomarker of photoreceptor-specific contrast sensitivity loss in patients with retinitis pigmentosa. Translational Relevance: We aim to develop tests of visual function for clinical trials of novel therapies for inherited retinal diseases from methods that can currently be used only in vision research labs.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Contrast sensitivity; Photoreceptors; Retinal dystrophy; Retinitis pigmentosa; Temporal vision